2021
DOI: 10.1186/s40537-021-00530-x
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning concepts for correlated Big Data privacy

Abstract: With data becoming a salient asset worldwide, dependence amongst data kept on growing. Hence the real-world datasets that one works upon in today’s time are highly correlated. Since the past few years, researchers have given attention to this aspect of data privacy and found a correlation among data. The existing data privacy guarantees cannot assure the expected data privacy algorithms. The privacy guarantees provided by existing algorithms were enough when there existed no relation between data in the datase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Biswas et al [14] suggested a more effective chaos-based system of cryptography for healthcare image encryption and decryption. They employed a complicated chaos-based PRNG for creating an exceptional secret key with an enhanced architecture that includes permutation, substitution, and diffusion features.…”
Section: Figure 2: Security Of Medical Images For Telemedicine: a Sys...mentioning
confidence: 99%
“…Biswas et al [14] suggested a more effective chaos-based system of cryptography for healthcare image encryption and decryption. They employed a complicated chaos-based PRNG for creating an exceptional secret key with an enhanced architecture that includes permutation, substitution, and diffusion features.…”
Section: Figure 2: Security Of Medical Images For Telemedicine: a Sys...mentioning
confidence: 99%
“…Previous studies employed data privacy techniques such as k-anonymity [1], l-diversity [2], t-closeness [3] and differential privacy [4]. However, those techniques can be complemented by considering data correlation, which possesses utmost significance while exploiting big data [5]. The heterogeneous characteristics underlying in OpenWiFi data possess identical traits of Big Data.…”
Section: Introductionmentioning
confidence: 99%
“…Big data technologies allow a lot amount of data to be accessed, collected, processed, transmitted and used more efficiently (Bentotahewa et al, 2021), also apparently get magnified privacy threats (Biswas et al, 2021) and bring complexity of privacy behaviors. The boundary of privacy concept has changed dramatically, and privacy is often defined as big data directly or indirectly carrying personal information (Tan and Pivot, 2015), in other words natural privacy (mainly including demographic information collected from single platform) and integrated privacy extracted from various online footprints with or without users' awareness and intention.…”
Section: Introductionmentioning
confidence: 99%
“…Big data technologies allow a lot amount of data to be accessed, collected, processed, transmitted and used more efficiently (Bentotahewa et al. , 2021), also apparently get magnified privacy threats (Biswas et al. , 2021) and bring complexity of privacy behaviors.…”
Section: Introductionmentioning
confidence: 99%